2019
DOI: 10.1111/jog.13993
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical outcomes after first‐trimester chorionic villus sampling in twin pregnancies: A retrospective case–control study

Abstract: Aim: Prenatal diagnostic testing by chorionic villus sampling (CVS) is sometimes recommended for women with twin pregnancies. However, few studies have compared the outcomes between twins with CVS and control twins without intervention. This study aimed to compare the obstetrical outcomes of CVS in twin pregnancies and those in non-intervention twin pregnancies. Methods: First-trimester transabdominal CVS was performed on dichorionic-diamniotic twins (n = 54; Group 1) between December 2006 and January 2017 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Brambati et al reported that the number of pregnancies with one or two fetal deaths at any gestational age after 7-12 weeks was 5/147 (3.4%) in the CVS group and 0/63 (0%) in controls; this study was confined to DC twins, and pregnancies undergoing embryo reduction or termination were excluded 10 . Kim et al reported that the number of pregnancies with one or two fetal deaths between 12 and 24 weeks' gestation was 4/54 (7.4%) in the CVS group and 6/155 (3.9%) in controls; this study was confined to DC twins, and pregnancies with a chromosomal anomaly or lethal fetal defect and those undergoing embryo reduction were excluded 11 . The small number of patients in these studies and the substantial heterogeneity between the studies preclude any meaningful conclusions being drawn from meta-analyses attempting to synthesize the existing evidence.…”
Section: Comparison With Other Studiesmentioning
confidence: 82%
See 2 more Smart Citations
“…Brambati et al reported that the number of pregnancies with one or two fetal deaths at any gestational age after 7-12 weeks was 5/147 (3.4%) in the CVS group and 0/63 (0%) in controls; this study was confined to DC twins, and pregnancies undergoing embryo reduction or termination were excluded 10 . Kim et al reported that the number of pregnancies with one or two fetal deaths between 12 and 24 weeks' gestation was 4/54 (7.4%) in the CVS group and 6/155 (3.9%) in controls; this study was confined to DC twins, and pregnancies with a chromosomal anomaly or lethal fetal defect and those undergoing embryo reduction were excluded 11 . The small number of patients in these studies and the substantial heterogeneity between the studies preclude any meaningful conclusions being drawn from meta-analyses attempting to synthesize the existing evidence.…”
Section: Comparison With Other Studiesmentioning
confidence: 82%
“…Kim et al . reported that the number of pregnancies with one or two fetal deaths between 12 and 24 weeks' gestation was 4/54 (7.4%) in the CVS group and 6/155 (3.9%) in controls; this study was confined to DC twins, and pregnancies with a chromosomal anomaly or lethal fetal defect and those undergoing embryo reduction were excluded 11 . The small number of patients in these studies and the substantial heterogeneity between the studies preclude any meaningful conclusions being drawn from meta‐analyses attempting to synthesize the existing evidence.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Four studies 24,28,34,35 (567 pregnancies) reported the overall risk of fetal loss in twin pregnancies undergoing CVS. Head‐to‐head meta‐analyses comparing directly women undergoing and those not undergoing CVS showed no significant difference in overall fetal loss (two studies 24,35 : 3/201 vs 5/218; OR,1.61 ( P = 0.5); RD, 0.003 ( P = 0.8)); all cases of fetal loss occurred before 24 weeks of gestation and analysis of the rate of fetal loss before 24 weeks therefore demonstrated the same results (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Table S2 shows the definition of overall fetal loss, the indication for invasive prenatal diagnosis and the exclusion criteria in each of the included studies. These 16 studies 9,10,23–36 included 3419 twin pregnancies undergoing an invasive procedure and 2517 twin pregnancies not undergoing invasive prenatal diagnosis. Twin pregnancies included both DC and MC pregnancies; however, we could not find any study reporting the occurrence of fetal loss exclusively in monoamniotic gestations.…”
Section: Resultsmentioning
confidence: 99%